A comparative study on the hydrodynamics of liquidâliquid hydrocyclonic separation - Al-Kayiem, H.H. (WITPress, 2014)
The productivity of wells with a higher waterâoil ratio can be improved by the use of a liquidâliquid hydrocyclone separator in the downhole. This system presents an excellent water flooding technique as the water separated downhole is pumped back into the same formation. The produced fluid undergoes a lot of orientations and motions from the time it enters the hydrocyclone until it exits the outlets. This paper helps bring to light the hydrodynamics of the liquidâliquid hydrocyclones, explaining how the fluid behaves once it is within the hydrocyclone, in order to achieve efficient separation. Analytical solutions were used to analyse some of the important flow pattern phenomenon within the liquidâliquid hydrocyclone. The fluid properties considered in this work are similar to that of the Malaysian Bayan offshore field. The results showed that the flow reversal radius was paramount in determining the separation efficiency. There were two existing swirling zones. In the inner zone the light fluid fraction is spiralling upwards, while in the outer zone the heavier fluid fraction is spiralling downward against the walls of the hydrocyclone. Â© 2014 WIT Press.